Along a long road - Viva, Frank (HarperCollins Publishers, 2011)
Illustrations and brief text evoke a bicycle ride, with its ups and downs, sweeping turns, and vivid views
Keywords: Ausflug; Radfahren; Straße; Bilderbuch